Manajemen Pembinaan Prestasi Pada Klub Bulutangkis Se-Kabupaten Wonosobo - Williyanto, Septian (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2016)
The type of this research is a quantitative with descriptive approach/ survey. Based on resultof the research, it know that the founding program in the ABS Club, BST, Indoraya, and Tunas Perkasa have run well. Whereas for Baker Club and Mutiara haven’t run well because both of club haven’t do tryout program. The management system in a BST club have goodmanagement because it have a good active organization.While, for the ABS club, Baker, Indoraya, Mutiara, and Tunas Perkasa haven’t run well because of personal managed. The program of exercise that be done of ABS club, Baker, BST, Indoraya and Tunas Perkasa haverun well. While for a Mutiara club haven’t run well and must add some exercise schedule.Facilities and Infrastructures of the ABS and BST club have a good because it facilitate by fitness center for supporting exercise program. Although, for Baker club, Indoraya, Mutiara,and Tunas Perkasa is still not enough and need some add some facilities. Funding in ABS and Baker club have good because it have sponsor however for BST club, Indoraya, Mutiara, andTunas Perkasa haven’t not good. The conclusion of the research is the founding management that running by badminton club in Wonosobo Regency in years 2015 not maximumenough.